(3GdeMQQs - (3YHO GdSdGe Hf YHO Gddg Hf GdNVQ Hf eMeO, eLO GdOjf CHh GdHQcGJ GHf JjejI GdMQGfj,J (B652 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH ai Gdabg Ydi ePgH GdEeGe CHj YHO Gddg CMeO Hf eMeO Hf MfHd GdTjHGfi s
(3BNQgG (B:s
(3hEf bGd OQge ai OjfGQ dReg OQge hEf bGd OQge ai YTQI dReg OQge s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1612s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs